Operational determination of the point of a short circuit in power lines - K. V. Suslov; N. N. Solonina; Z. V. Solonina; A. R. Akhmetshin (Известия высших учебных заведений: Проблемы энергетики)
RELEVANCE. An urgent task is to improve the reliability and quality of power supply. Very often, failures in operation are caused by damage to overhead and cable lines. Traditionally, a fairly large number of violations occur in the share of electrical distribution networks. For the reliable functioning of power systems and uninterrupted power supply to consumers, it is necessary to identify and eliminate faults in a short time to minimize damage. Thus, a method for efficient, accurate and reliable fault location is needed for both utility companies and consumers. To solve this problem, it is necessary to quickly obtain information about the state of the distribution eclectic network.   THE PURPOSE. Reducing the time to search for a fault location in electrical networks, reducing damage from downtime for undersupply of electricity by analyzing existing methods for determining the location of faults on a power transmission line and developing a method for its prompt detection in electrical networks.   METHODS. The basis of this method is a preliminary theoretical calculation of short-circuit currents in various sections of a power line. Based on the values obtained as a result of the calculation, the measured values of the short-circuit currents are compared with these values, on the basis of which the location of the line damage is determined. An algorithm for searching the left and right boundaries of the short-circuit current value in an ordered array of statistical data has been developed.   RESULTS. A method for quickly determining the location of a short circuit is proposed, which is based on the use of a data array of theoretically calculated short circuit currents. The presented algorithm is able to accurately determine the coordinates of the short circuit in electrical networks.   CONCLUSION. The proposed method for determining the location of damage to the power line allows you to increase the efficiency of determining the point of a short circuit and thereby reduce the time to eliminate the accident, and therefore, economic losses from undersupply of electricity.The basis of this method is a preliminary theoretical calculation of short-circuit currents in various sections of a power line. Due to the subsequent comparison of the measured values of short-circuit currents with the values of the calculated values, the location of the damage to the power line is determined. The presented algorithm is designed to accurately determine thecoordinates of the short circuit location, which can significantly reduce the search time and improve the accuracy of determining the fault location in the range from 100 to 150 m, regardless of the length of the power line, which significantly reduces the time to search for damage at the same time as solving the problem of reducing downtime , as well as minimizing damage both for guaranteeing suppliers represented by electric grid companies, and for consumers represented by industrial and agricultural enterprises.